Real Life Efficacy and Safety of Secukinumab in Biologic-Experienced Patients With Psoriatic Arthritis - Klavdianou, Kalliopi; Lazarini, Argyro; Grivas, Alexandros; Tseronis, Dimitrios; Tsalapaki, Christina; Rapsomaniki, Panagiota; Antonatou, Katerina; Thomas, Konstantinos; Boumpas, Dimitrios; Katsimbri, Pelagia; Vassilopoulos, Dimitrios (Frontiers in Medicine, 2020)
Background: Real world evidence data regarding secukinumab (SEC) use in biologic-experienced patients with psoriatic arthritis (PsA) are scarce. Objectives: To assess the real life survival, safety and efficacy of SEC in biologic-experienced patients with PsA. Methods: All biologic-experienced PsA patients treated with SEC in 2 University Rheumatology Units were included (3/2016-12/2018). Patients’ and disease characteristics were recorded at baseline and during SEC therapy. Results: 75 patients were included; 76% were females with a mean age of 53.9 years, median disease duration of 6.7 years and median SEC treatment duration of 11.1 months. At baseline, 97% had peripheral arthritis, 42% axial involvement, 22% enthesitis and 12% dactylitis. Regarding previous biologic exposure, 48 (64%) had been exposed to anti-tumor necrosis factor (TNF) agents only, 5 (7%) to the interleukin (IL)-12/23 inhibitor (Ustekinumab-UST) only while 22 (29%) both to anti-TNFs and UST. 53% received SEC in combination with non-biologics and 35% with glucocorticoids, respectively. During follow-up, statistically significant improvement in different disease activity indices were noted (DAS28-CRP, DAPSA, BASDAI). SEC survival rate at the end of follow-up was 64% (48/75), without difference between patients exposed to anti-TNFs only (67%) vs. anti-TNFs and UST (68%) as well as to 1 vs. ≥2 anti-TNFs. The rate of serious adverse events and serious infections during follow-up was 4.8 and 1.2/100 patient-years, respectively. Discussion: In real life, in biologic-experienced patients with PsA, SEC displayed a high retention rate, regardless of the type and number of previous biologics (anti-TNFs ± anti-IL12/23), without significant side effects.